2008
DOI: 10.5641/193250308x13086832906111
|View full text |Cite
|
Sign up to set email alerts
|

Beating the Bunker: The Effect of PETTLEP Imagery on Golf Bunker Shot Performance

Abstract: The aim of this study was to compare the effects of physical practice with PETTLEP-based (Physical, Environment, Task, Timing, Learning, Emotion and Perspective; Holmes & Collins, 2001) imagery and PETTLEP + physical practice interventions on golf bunker shot performance. Thirty-two male county- or international-level golfers were assigned to one of four groups; PETTLEP imagery, physical practice, PETTLEP + physical practice, or control. The PETTLEP imagery group imaged 15 bunker shots, their interventions inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…Such studies have found PETTLEPbased interventions to be the more effective (Potter, Devonport & Lane, 2005;Smith, Wright, Allsopp & Westhead, 2007;, using tasks such as the hockey penalty flick, the long jump, a gymnastics jump and a strength task (bicep curl). In addition, Wright, Smith and Cantwell (2008) found that when very experienced (international and county level) amateur golfers replaced some of their physical practice of bunker shots with PETTLEP imagery, their performance improved more than that of golfers who continued with their full quota of physical practice of bunker shots.…”
Section: Brief Review Of Research Using the Pettlep Model: Issues Andmentioning
confidence: 99%
“…Such studies have found PETTLEPbased interventions to be the more effective (Potter, Devonport & Lane, 2005;Smith, Wright, Allsopp & Westhead, 2007;, using tasks such as the hockey penalty flick, the long jump, a gymnastics jump and a strength task (bicep curl). In addition, Wright, Smith and Cantwell (2008) found that when very experienced (international and county level) amateur golfers replaced some of their physical practice of bunker shots with PETTLEP imagery, their performance improved more than that of golfers who continued with their full quota of physical practice of bunker shots.…”
Section: Brief Review Of Research Using the Pettlep Model: Issues Andmentioning
confidence: 99%
“…The first involved amending the original script through a series of intermittent consultations with the participants, who were asked if they would like to make any additions or modifications to enhance the imagery experience and the individual meaning of the imagery (i.e. Smith, Wright, & Cantwell, 2008;Shearer, Mellalieu, Thomson, & Shearer, 2008).…”
Section: Sj Cooley Et Al: Methodological Variations In Guided Imagmentioning
confidence: 99%
“…Previous research suggests that an increased use of PETTLEP elements maximises the success of an imagery intervention (Smith et al, 2007(Smith et al, , 2008Wright & Smith, 2009). Thus, Smith (2011) advises that for maximum benefit, the PETTLEP model should be integrated as a whole, rather than in part.…”
Section: Pettlepmentioning
confidence: 99%
“…Other studies analyze the outcome from a mathematical perspective with a specific parametric analysis of distances and angles of the movements, e.g. in golf (Smith et al, 2008) and high jump (Olsson et al, 2008). A small number of researches in sport assess the final score of the movement or the number of successful attempts (Peynircioglu et al, 2000;Ploszay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%